2004
DOI: 10.1097/01.ccm.0000120055.52377.bf
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of aerosolized prostacyclin therapy in children with acute lung injury*

Abstract: Aerosolized prostacyclin improves oxygenation in children with acute lung injury. Future trials should investigate whether this treatment will positively affect outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 40 publications
1
68
0
Order By: Relevance
“…Primary outcome measure was oxygenation. It was found that oxygenation was significantly improved by 26% [143]. The optimal dosage in children for PGI 2 was 30 ng/kg/min and thus higher than the recommended dosage in adult patients of 10 ng/kg/min [145;146].…”
Section: Aerosolized Prostacyclinsmentioning
confidence: 99%
“…Primary outcome measure was oxygenation. It was found that oxygenation was significantly improved by 26% [143]. The optimal dosage in children for PGI 2 was 30 ng/kg/min and thus higher than the recommended dosage in adult patients of 10 ng/kg/min [145;146].…”
Section: Aerosolized Prostacyclinsmentioning
confidence: 99%
“…But although the use of iEPO has gained popularity since it was first publicized for the treatment of ARDS in 1993, substantial efficacy data are lacking [Walmrath et al 1993]. Literature evaluating its use have been few and thus no studies have evaluated mortality as a primary endpoint [Zwissler et al 1996;Walmrath et al 1996;van Heerden et al 2000;Dunkley et al 2013;Domenighetti et al 2001;Dahlem et al 2004]. While commonly used as a therapy of final resort, a gap in the literature has led to controversy surrounding iEPO in regards to optimal dosing and safety, as well as the target patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Epoprostenol initiates a cascade resulting in vasodilation of pulmonary vascular beds promoting blood flow to areas of active ventilation [Zwissler et al 1996]. While certain strategies such as protective lung ventilation, prone positioning and neuromuscular blockade have literature suggesting benefit in ARDS patients, SPVs have failed to do so in clinical research and are commonly reserved for patients failing to respond to these therapies [Papazian et al 2010;Slutsky, 2010;Beitler et al 2014;Goffi and Ferguson, 2014;The ARDS Network, 2000;Walmrath et al 1996;van Heerden et al 2000;Dunkley et al 2013;Domenighetti et al 2001;Dahlem et al 2004;Torbic et al 2013].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, iloprost was as efficacious as iNO for infants with pulmonary hypertension and congenital heart defects but was not synergistic with iNO [61]. 14 infants and children with acute lung injury received nebulised epoprostenol and oxygenation improved with NNT 51.8 [63]. Since all these molecules are liquid, nebulisation is needed.…”
Section: Pulmonary Vasodilatorsmentioning
confidence: 99%